Metastatic prostate cancer presenting as a rapidly increasing gluteal muscle mass at an intramuscular injection site (2022)
Prostate cancer is the second commonest male cancer globally. However, diagnosis may be delayed or missed due to atypical presentations such as metastases to unusual sites. The axial skeleton, lymph nodes, and viscera are the common sites for prostate cancer metastasis with skeletal muscles being uncommonly affected, and until now there has been no report of metastasis to the gluteal muscles from the disease. We present the case of a 78-year-old man with no lower urinary tract symptoms who presented with a 2-year history of a right supra-gluteal mass at the site of an intramuscular injection hematoma/abscess that rapidly increased in size 5 months prior to presentation and an abnormal gait. CT and MRI scans were suggestive of a malignant mass (possibly a rhabdomyosarcoma) and enlarged multinodular prostate with bilateral lymphadenopathy. A biopsy of the gluteal mass confirmed metastatic adenocarcinoma with the colon or the prostate being possible primaries. His serum PSA was markedly elevated (3441 ng/ml) but his other tumor markers were normal. Prostate biopsies confirmed a Gleason 4+3=7 prostate cancer and ADT was commenced. He responded well and remains in good health 15 months into his treatment with a marked reduction in the size of his gluteal mass and a restoration of a normal gait. His serum PSA and Testosterone are presently 2.4 ng/ml and 0.3 mmol/L respectively.